1999
DOI: 10.1046/j.1523-5378.1999.09016.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Endoscopic Findings for the Diagnosis of Helicobacter pylori Infection: Evaluation in a Country with High Prevalence of Atrophic Gastritis

Abstract: The accurate endoscopic assessment of gastritis according to the Sydney system along with gastric fold findings and the endoscopically identified extent of gastric atrophy are valuable indicators for determining H. pylori infection and histologic gastritis in the Japanese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
91
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 22 publications
4
91
0
2
Order By: Relevance
“…It is well known that H. pylori infection causes endoscopic gastritis with persistent infection, presenting as erythema, erosion, haemorrhagic and large gastric folds. 16 Several studies [17][18][19] have shown that eradication of H. pylori improves H. pylori-related endoscopic gastritis as well as histological gastritis. Therefore, improvement in endoscopic gastritis with eradication of H. pylori might have contributed to the detection of potential gastric cancer within 48 months after eradication in our DU, duodenal ulcer; GU, gastric ulcer; AG, atrophic gastritis; GCa, gastric cancer; ER, endoscopic resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that H. pylori infection causes endoscopic gastritis with persistent infection, presenting as erythema, erosion, haemorrhagic and large gastric folds. 16 Several studies [17][18][19] have shown that eradication of H. pylori improves H. pylori-related endoscopic gastritis as well as histological gastritis. Therefore, improvement in endoscopic gastritis with eradication of H. pylori might have contributed to the detection of potential gastric cancer within 48 months after eradication in our DU, duodenal ulcer; GU, gastric ulcer; AG, atrophic gastritis; GCa, gastric cancer; ER, endoscopic resection.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, all patients with gastric cancer discovered after eradication had severe baseline mucosal atrophy in the corpus, and the gastric cancers were mainly early non-cardiac cancers of the intestinal type with ulcers. Atrophic gastritis and gastric cancer are common in Japan, 16,20,21 and this highlights need for careful endoscopic follow-up. Recent studies showed that eradication of H. pylori contributes to the chemoprevention of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory process is initially superficial but, in sequence, affects the entire mucosa, first in the antrum and progressing proximally to the body. Over the years, the gastric glands are destroyed showing epithelial atrophy and intestinal metaplasia areas that favor the appearance of gastric carcinoma [2] . The diagnosis of the infection requires at least two tests in accordance with the European guidelines [3] .…”
Section: Introductionmentioning
confidence: 99%
“…The gastroscopic findings of H. pylori infected gastric mucosa were erythema, erosions, antral nodularity, thickened gastric folds, and visible submucosal vessels. However, these findings are not a reliable method of diagnosis because of their low sensitivity and specificity (Laine et al, 1995;Bah et al, 1995;Mihara et al, 1999;Redeen S et al, 2003). In 2010, Taiwanese endoscopist a study using close-up observation between the endoscope tip and the gastric mucosa and found the "mosaic pattern" in the corpus mucosa.…”
Section: Introductionmentioning
confidence: 99%